Live Streaming and Influencer Review on Purchase Decision: The Mediating Effect of Consumer Confidence in E-Commerce - Hazmanan Khair; Satria Tirtayasa; Fajar Pasaribu; Cahyani Syafitri (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid growth of e-commerce has encouraged businesses to adopt digital marketing strategies such as live streaming and influencer reviews to influence consumer purchasing behavior. However, limited studies have examined the mediating role of consumer confidence, particularly in the context of health supplement products characterized by high perceived risk. This study aims to analyze the effects of live streaming and influencer reviews on purchase decisions and investigate the mediating role of consumer confidence. A quantitative approach was employed using an associative research design with purposive sampling. Data were collected from 384 consumers in Medan Denai. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that live streaming significantly influences both purchase decisions and consumer confidence, while influencer reviews significantly enhance consumer confidence but do not directly affect purchase decisions. Consumer confidence significantly influences purchase decisions and mediates the relationships between live streaming, influencer reviews, and purchase decisions. These findings highlight the importance of consumer confidence as a psychological mechanism that transforms digital marketing activities into purchasing behavior. The study contributes to digital marketing literature and provides practical insights for e-commerce businesses in developing strategies that strengthen consumer confidence to improve purchasing decisions.